Italy, the people - Nickles, Greg (New York : Crabtree, 2001)
Describes the people of Italy, how they live, where they work, and how they spend their leisure time.
Includes index.
AR
3-7.
6.6.
Accelerated Reader
Keywords: Italy -- Social life and customs; Italy -- History